A Comparative Ex Vivo Study of Plasminogen Activators and Proteases for Fibrinolytic Activity and Side Effects in Rabbits - Janik, B. A; Papaioannou, S. E (Thrombosis and Haemostasis, 1977)
Urokinase, streptokinase, Brinase, trypsin, and SN 687, a bacterial exoprotease, have been evaluated in an ex vivo assay system. These enzymes were injected into rabbits and the fibrinolytic activity as well as other coagulation parameters were measured by in vitro techniques. Dose-response correlations have been made using the euglobulin lysis time as a measure of fibrinolytic activity and the 50% effective dose has been determined for each enzyme. Loading doses, equal to four times the 50% effective dose, were administered to monitor potential toxicity revealing that Brinase, trypsin, and SN 687 were very toxic at this concentration.Having established the 50% effective dose for each enzyme, further testing was conducted where relevant fibrinolytic and coagulation parameters were measured for up to two days following a 50% effective dose bolus injection of each enzyme. Our results have demonstrated that urokinase and streptokinase are plasminogen activators specifically activating the rabbit fibrinolytic system while Brinase, trypsin and SN 687 increase the general proteolytic activity in vivo.The advantages of this ex vivo assay system for evaluating relative fibrinolytic potencies and side effects for plasminogen activators and fibrinolytic proteases have been discussed.